A new large-bodied Pliocene seal with unusual cutting teeth - Rule, James P.; Adams, Justin W.; Rovinsky, Douglass S.; Hocking, David P.; Evans, Alistair R.; Fitzgerald, Erich M. G. (Royal Society open science, 2020)
Today, monachine seals display the largest body sizes in pinnipeds. However, the evolution of larger body sizes has been difficult to assess due to the murky taxonomic status of fossil seals, including fossils referred to Callophoca obscura , a species thought to be present on both sides of the North Atlantic during the Neogene. Several studies have recently called into question the taxonomic validity of these fossils, especially those from the USA, as the fragmentary lectotype specimen from Belgium is of dubious diagnostic value. We find that the lectotype isolated humerus of C. obscura is too uninformative; thus, we designate C. obscura as a nomen dubium. More complete cranial and postcranial specimens from the Pliocene Yorktown Formation are described as a new taxon, Sarcodectes magnus . The cranial specimens display adaptations towards an enhanced ability to cut or chew prey that are unique within Phocidae, and estimates indicate S. magnus to be around 2.83 m in length. A parsimony phylogenetic analysis found S. magnus is a crown monachine. An ancestral state estimation of body length indicates that monachines did not have a remarkable size increase until the evolution of the lobodontins and miroungins.